The demands for environmental regulation and for trade in the presence of private mitigation - Louis Hotte; Stanley L. Winer (Center for Economic Studies and ifo Institute (CESifo), 2008)
We study the nature of individual demands for environmental regulation and for trade openness in the general equilibrium of a small open economy where the environment is an input to production. Differences in the ability of individuals to afford private mitigation of the adverse consequences of pollution is a central feature of the analysis. Private mitigation leads to an endogenous, unequal distribution of the health-related consequences of pollution across income groups in a manner consistent with epidemiologic studies, in contrast to much of the literature which assumes equal health effects for all. We show that when private mitigation is possible at a cost, trade polarizes the interests of rich and poor with respect to the stringency of regulation. Moreover, even though trade has the potential to benefit everyone, the poor may oppose trade openness because of a concern that laxer environmental regulation will then be imposed in the interest of the rich. We explain why heterogeneity in the intensity of preferences, and not just in their direction, is likely to play a role in the determination of collective choices with respect to the regulation of the environment and of trade. We conclude by drawing out the implications of the analysis for the study of the political economy of the environment-trade-welfare nexus.
Keywords: D7; F18; Q56; 330; Regulation; environment; pollution; private mitigation; trade; welfare; health; collective choice; Umweltschutz; Freihandel; Regulierung; Public Choice; Wohlfahrtseffekt; Kleines-offenes-Land